Detection of Skeletonema costatum based on loop-mediated isothermal amplification combined with lateral flow dipstick. (December 2017) - Huang, Hai-Long; Zhu, Peng; Zhou, Cheng-Xu; Yan, Xiao-Jun; Zou, Yi-Xin; Lv, Pei-Wen
Abstract: We developed a new assay method, which combines loop-mediated isothermal amplification (LAMP) with a chromatographic lateral flow dipstick (LFD) for the rapid and special detection of the diatom Skeletonema costatum . Four groups of LAMP primers were derived from a conserved DNA sequence unique to S. costatum . The amplifications were carried out at 61, 63, and 65 °C for 60 min in various combinations by the quantitative PCR thermal cycler to confirm optimal primers and reaction temperature. The LAMP-LFD detection limit was 0.94 pg/μL of S. costatum genomic DNA and was 100 times more sensitive than conventional PCR. The LAMP-LFD method had high specificity and accurately identified S. costatum algal isolates, but not other algal isolates. The new LAMP-LFD assay can be used as a reliable and easy method to detect S. costatum. Highlights: The LAMP-LFD method showed a high specificity. The detection limit of LAMP-LFD was 100 times more sensitive than standard PCR. The LAMP-LFD assay can be used as a reliable method for detection of S. costatum. The first report of LAMP-LFD assay established in harmful algae of S. costatum. The LAMP-LFD method is more ideal for on-site detecting.